Pelatihan Komunikasi Efektif Kader Posyandu dan Opinion Leader dalam Upaya Penanganan Stunting di Gampong Paloh Punti Kota Lhokseumawe - Cut Andyna; Muhammad Fazil; Muchlis; Rizka Mulyawan (Jurnal Solusi Masyarakat (JSM), 2026)
Posyandu cadres are at the forefront of handling stunting due to their direct involvement in the community. In addition to driving participation in environmental prevention and empowerment efforts, Posyandu Cadres also provide assistance, education and early detection in stunting cases. This then positions the Cadre to have a strategic role in monitoring maternal and child health. For this great responsibility, Posyandu Cadres need to have skills in communication. This will be the foundation for cadres to conduct health education, build trust and correct misinformation. With good communication, cadres can have a greater impact on maternal and child health, including reducing the number of stunting cases. Therefore, this communication training activity was carried out to answer the anxiety of Posyandu Cadres who felt unconfident in carrying out their duties and roles. This activity was initiated by PT PHE NSO as a form of social responsibility, especially in its operational area by collaborating with the Oil and Gas Center. This program is part of the assistance to the Paloh Punti Village Posyandu which has previously supported the Supplementary Feeding (PMT) to the vulnerable target groups, namely pregnant women who experience Chronic Energy Deficiency (KEK) and toddlers who are malnourished or do not gain weight. This training will not only equip cadres technically but also conceptually in designing educational strategies that are communicative and empathetic to the needs of the community so as to encourage the achievement of active family involvement in dealing with stunting.